Effects of sensory garden-based activities on attention and impulse control of children with autism - Asinas, Claudinne D.; Vidal, Lutze-sol A. Vidal; Zamora, Maria Cecilia V.; Magtoto, Frances Olivia M. (Quezon City College of Education, University of the Philippines Diliman, 2019)
The study aimed to determine the effects of sensory garden-based activities on the attention and impulse control of five children with autism, ages 7 to 12 years old. It is a qualitative research that used a multiple baseline design across two settings. The study documented frequencies of inattentive (i.e., off-task, atypical motoral behaviors, and atypical verbal behaviors) and impulsive behaviors (i.e., bodily impulses, getting emotional, getting physical, off-seat behaviors, and sudden utterance) which were recorded during baseline and interventions phases. Graphs, tables and narrative reports were used to establish the effects of the intervention. After engaging in sensory garden-based activities for 10 sessions, improvements were observed on the attention in the classroom of four out of five participants and on the impulse control of two out of five participants. On the other hand, three of the five participants showed inconsistent improvements in the frequencies of their impulsive behaviors. However, the changes in the degree and intensity of their impulsive behaviors were reported by the teachers to be positive. Further research may be undertaken on the effects of sensory garden-based activities on behaviors other than inattention and impulsivity (e.g., anxiety, hyperactivity, aggression), and in other developmental areas of concern (e.g., fine-motor, gross-motor, language-communication, psychosocial, academic achievement, self-care and independence training).
Thesis (Master of Arts in Education - Special Education)--University of the Philippines, Diliman
Includes bibliographical references.
Keywords: Autistic children -- Education -- Philippines; Special education -- Activity programs -- Philippines; Gardening -- Philippines